Perencanaan Peningkatan Daya Dukung dan Perpanjangan Runway untuk Mendukung Penerbangan Internasional di Bandar Udara Adi Soemarmo-Surakarta Menggunakan Software FAARFIELD dan COMFAA - Saraswati, Megananda; Negara Dalimunthe, Aditia Kesuma (Publica Scientific Solution, 2024)
Surakarta City or often called Solo is one of the areas in Central Java Province that has many international events every year. The implementation of international events also means that the participants come from abroad. The city of Solo has one airport that is accessed by foreign participants, namely Adi Soemarmo - Surakarta Airport. Adi Soemarmo Airport has one runway facility of 2500x45 m with a PCN value of 68 F/C/X/T. Based on historical data for international airplanes can land at Adi Soemarmo Airport - Surakarta with maximum weight restrictions by reducing aircraft fuel so that they have to stop at Kuala Lumpur Airport - Malaysia for refueling. Therefore, it is necessary to increase the PCN value and adjust the runway dimensions so that it can accommodate Airbus A330-900 aircraft with maximum load so that it can carry out direct flights to Jeddah, Mecca. Based on the results of data analysis using the ARFL method, FAARFIELD and COMFAA software, to be able to serve direct flights to Jeddah, a 534 m runway extension and 5.1 cm overlay are required so that the PCN value will increase to 135.3 F/C/X/T.